Building virtual collection and Spanish colonial imprints of the Philippines. (16th January 2020) - Pendse, Liladhar R.
Abstract : Purpose: The access to the rare originals of the early Spanish colonial imprints of the Philippines remains problematic. The reference librarians often are restricted to directing the students and scholars to the secondary resources that are available both in print and as a part of the digital assets within the North American academic libraries. This paper aims to focus on the select primary source editions including select Spanish language colonial imprints that are available electronically on the Web along the Open Access. These Web-based resources serve as the reference tools for the early history of the Philippines and Southeast Asia. As many of these publications are rare and extremely expensive for most libraries, the Open Access resources serve as an aid to building a virtual collection of these items. Design/methodology/approach: The author had to create a data set of the early imprints of the Spanish Philippines using several bibliographic resources. The data set will be submitted as an Appendix for this research paper. The author did both qualitative and quantitative analysis of the data set along with the voyant-based digital humanities approach for topic modeling. Findings: The goals of this paper were to not only survey the early Spanish printing of the Philippines but also provide the reader with a somewhat complete picture of how the printing began in the Spanish Philippines, what kind of the first books were printed and how one can access them given their rarity and fragility. The collection building paradigms are undergoing significant shifts, and the focus of many academic libraries is shifting toward providing access to these items. As these items high-value low-use items continue to be part of the Special Collections, the access to these is problematic. The virtual collections thus serve as a viable alternative that enables further research and access. While the creators of these works are long gone, the legacy of the Spanish colonial domination, printing and the religious orders in the Philippines remain alive through these works. Research limitations/implications: As this is an introductory paper, the author focused on the critical editions rather than providing a comprehensive bibliographic landscape of the presses that produced these editions. He also did not take into consideration many pamphlets that were published in the same period. He also did not consider the Chinese language publications of the Islands. The Chinese had been block printing since medieval times (Little, 1996). In the context of the Spanish Philippines, the Chinese migration and trade have been studied in detail by Chia (2006), Bjork (1998) and Gebhardt (2017). The scope of this paper also was centered toward building a virtual collection of these rare books. Practical implications: Rare books are often expensive and out-of-reach for many libraries; the virtual collection of the same along the Open Access model represents an alternative to collect and curate these collections. The stewardship of these collections also acquires a new meaning in the digital milieu. Social implications: This research paper will allow scholars to see past the analog editions and help them focus on curating a virtual collection. The questions of electronic access are often ignored when it comes to visiting and using them in a controlled environment of the reading room in the Special Collections. The author argues that one way to enable access to these rare and expensive books is to provide access to their digital counterparts. These digital/virtual surrogates of the originals will facilitate further research. Originality/value: The author could not find similar research on the publications of the early Spanish colony of the Philippines.